Yeni Kültepe vesikalannın ışığında Anadolu-Asur siyasi münasebetleri ve yerli idarede yemin usulü - Bilgiç, Emin
Abstracts; The Appraisal of the Political Relations between Anatolia and Assyria in the Light of New Kültepe Documents and the Treaty Foundations in the Indigenous Administration